Mean square error of the traditional replacement for the linear mechanical system - Anh, Nguyen Dong (Vietnam Journal of Mechanics, 1993)
The error between mean square responses of the original mechanical linear system and the system obtained by using the traditional replacement is investigated. As a result, a modified replacement is proposed which gives zero-error for the mean square responses.